Highly Educated Mother's Perception of Childhood Vaccination Hesitancy in Kazakhstan: A Thematic Analysis - Togzhan Abdirakhman; Ejercito Balay-Odao; Mohamad Aljofan; Jonas Cruz (Shiraz University of Medical Sciences, 2024)
Background: Vaccine hesitancy among parents directly affects the child's vaccination status sincethey are the legal decision-makers regarding vaccinating their children. The study aimed to describethe perceptions of highly educated Kazakhstani mothers about childhood vaccination hesitancy.Methods: The study utilized a thematic analysis to explore the mothers' perceptions. A sample of95 participants comprehensively answered the free-text questions in an online questionnaire fromJanuary to February 2023. The analysis of the free-text responses followed a semantic thematicanalysis approach. The data were coded manually.Results: From the in-depth analysis of the data, 285 initial codes were extracted. The combination ofsimilar meanings and concept codes led to 14 sub-themes and finally yielded four significant themes:misconceptions about childhood vaccination, fear of the effect of vaccine on children, distrust of thehealthcare system, and social learning factors.Conclusion: The perceptions of Kazakh mothers about childhood vaccination hesitancy may leadto behaviors of delaying and refusing some or all childhood vaccines. Therefore, motivational andeducational strategies can be used by healthcare providers to instill trust in parents about childhoodvaccines and their safety and effectiveness.